Restorative Justice as a Policy Approach to Traffic Crime Resolution in Indonesia - Ketut Sukewati Lanang Putra Perbawa; Paul Atagamen Aidonojie (Lembaga Contrarius Indonesia, 2025)
Traffic crimes in Indonesia have shown a consistent increase, often leading to material damage, physical injury, and loss of life. The conventional criminal justice system, which predominantly emphasizes retributive punishment, has proven insufficient in addressing the underlying causes of traffic offenses and in delivering substantive justice for both victims and offenders. In light of these challenges, restorative justice offers a promising alternative approach that prioritizes reconciliation, offender accountability, and the restoration of social harmony. This research aims to examine the urgency and feasibility of adopting restorative justice as a policy framework for resolving traffic crimes in Indonesia. Employing normative legal research methods, the study is based on secondary data derived from statutory regulations, legal literature, and doctrinal analysis. The results indicate that Indonesian traffic law does not yet explicitly incorporate restorative justice principles, despite their proven effectiveness in other jurisdictions for handling minor and non-violent offenses. Practices such as mediation and victim-offender dialogue have demonstrated success in reducing recidivism and enhancing victim satisfaction. The study concludes that integrating restorative justice into traffic crime resolution could reduce case backlogs, restore community trust in the legal system, and promote a more compassionate, efficient approach to justice. Comprehensive legal reform and institutional readiness are essential for effective implementation.